The role of engagement in determining satisfaction: A study on educational organization - Pramono, Suwito Eko; Isdaryanti, Barokah; Diteeyont, Watsatree; Plangsorn, Boonrat; Wijaya, Angga Pandu (Kasetsart Journal of Social Sciences, 2023)
The Corona pandemic outbreak has resulted in the need for online learning. The online learning process needs accurate measurement; therefore, the research explores the influence of situational context and self-regulation on student engagement in the learning process and its implications for student satisfaction. This study was conducted at universities in Indonesia involving 134 research respondents. The results show self-regulation and situational context influence student satisfaction through learning engagement. The results demonstrate a direct effect of situational context on student satisfaction. The study’s results represent that learning engagement plays an essential role in the learning process. Based on the research result, the interaction between lecturers and students leads to learning satisfaction. The research provides a valuable insight that the learning process needs to involve students. Hence lecturers need to prepare various teaching materials online to motivate students to be continuously involved in the learning process.